PERAN PEMERINTAH DESA KEDITAN DALAM PEMBANGUNAN PARIWISATA - Lili, Lestari Oktalion; Lasso, Aldi Herindra (Universitas Kristen Satya Wacana, 2020)
Tourism is one of the vital economic sectors for local communities in Indonesia this makes the tourism development in every region is growing rapidly. However, there are obstacles faced during the development, so it requires interventions from local government to assist and support the local people. Using a qualitative approach, this research aims to examine the role of the village government in Keditan Village, District of Ngablak, Magelang Regency, in increasing support of people towards the ongoing tourism development. The result of the research shows that the government of Keditan have taken the role in supporting the people, but such role is not yet optimal. Researcher sees that it needs some further mentoring from stakeholders to support the village government to implement that role.